Prove By induction that sinx + sin3x + sin5x +.... Sin(2n-1) =sin^2(nx)/sin3x

In the denominator it should be sinx

do as with all inductions.

show that it's true for n=1

sinx = sin^2(x)/sin3x
Nope, not true.

So, how about n=2?
sinx+sin3x = sin^2(2x)/sin3x
Nope.

Better fix this and come back.

To prove the given statement using mathematical induction, we need to follow the three steps of the induction process: the base case, the induction hypothesis, and the inductive step.

Step 1: Base Case
The base case is typically when n = 1. We will verify whether the given equation holds true for this case.

Let n = 1:

sin(x) = sin^2(1x) / sin(3x)
sin(x) = sin^2(x) / sin(3x) (since 1x = x)

This equation is indeed true, so the base case holds.

Step 2: Induction Hypothesis
Assume that the given equation is true for some positive integer k, so we assume that:

sin(x) + sin(3x) + sin(5x) + ... + sin((2k-1)x) = sin^2(kx) / sin(3x)

It is important to note that we assume this statement is true for k = n, and we will attempt to prove it for k = n+1 in the next step.

Step 3: Inductive Step
We need to prove that if the equation is true for k = n, it must also be true for k = n+1.

Let's assume the equation is true for k = n:

sin(x) + sin(3x) + sin(5x) + ... + sin((2n-1)x) = sin^2(nx) / sin(3x) (Induction Hypothesis)

Now, we need to prove it for k = n+1:

sin(x) + sin(3x) + sin(5x) + ... + sin((2n-1)x) + sin((2n+1)x) = sin^2((n+1)x) / sin(3x)

To prove this, we can start from the left-hand side (LHS) and try to manipulate it to match the right-hand side (RHS).

LHS:
sin(x) + sin(3x) + sin(5x) + ... + sin((2n-1)x) + sin((2n+1)x)

We can rewrite this by factoring out sin((n+1)x):

sin(x) + sin(3x) + sin(5x) + ... + sin((2n-1)x) + sin((2n-1)x + 2x)

Using the sum-to-product formula for sine, we can rewrite sin((2n-1)x + 2x) as:

sin((2n-1)x + 2x) = sin((2n-1)x)cos(2x) + cos((2n-1)x)sin(2x)

We can now rewrite the LHS as:

(sin(x) + sin(3x) + sin(5x) + ... + sin((2n-1)x)) + (sin((2n-1)x)cos(2x) + cos((2n-1)x)sin(2x))

Using the Induction Hypothesis:

(sin^2(nx) / sin(3x)) + (sin((2n-1)x)cos(2x) + cos((2n-1)x)sin(2x))

We need to manipulate this expression further to match the RHS:

LHS:
(sin^2(nx) + sin((2n-1)x)cos(2x) + cos((2n-1)x)sin(2x)) / sin(3x)

To manipulate this further, we need to use trigonometric identities. Let's use the identity sin(a + b) = sin(a)cos(b) + cos(a)sin(b). If we let a = (2n-1)x and b = 2x, we get:

sin((2n-1)x + 2x) = sin((2n-1)x)cos(2x) + cos((2n-1)x)sin(2x)

Notice that this is the same expression as before. Therefore, we can rewrite the LHS as:

(sin^2(nx) + sin((2n-1)x + 2x)) / sin(3x)

Using the sum-to-product formula for sine again:

(sin^2(nx) + sin((2n-1)x + 2x)) / sin(3x) = (sin^2(nx) + sin((2n+1)x)) / sin(3x)

Finally, we have arrived at the RHS:

RHS:
sin^2((n+1)x) / sin(3x)

Since the LHS is equal to the RHS, we have shown that if the equation is true for k = n, then it is also true for k = n+1.

Therefore, by the principle of mathematical induction, the given statement is proven to be true for all positive integers n.